– The effect of the original letter (from) on the development of the meanings of the Holy Quran – A grammatical study - Idreis, Hamza Al - Zubair Ibrahim (Arab Journal for Sciences and Research Publishing, 2019)
The importance of this scientific paper: Come value as relevant to the Qur’an, by tracking the meanings "of" the original, from the words, and the views of scientists as evacuation. The main findings of the preposition (of the original) , through a variety of meanings, came meanings [of] the original, multiple, as follows: Beginning end spatial true, and starting end metaphors, and starting end, the moral, and the starting end, temporal, and Altbaad, and the statement of the race in addition to the names of species, and the wildcard, the reason or explanation, and preference.